Fresno County Bar Association with Carol Herbert, Dean San Joaquin College of Law - Watkins, Howard::::::::: (1983)
Fresno County Bar Association President-Elect Rodney Worrel, Dean Carol Herbert speaking at lectern re "Women in Transition" Fresno Hilton signage on lectern